Contrary to popular opinion - Dershowitz, Alan M. 1938- (Pharos Books, 1992)
"In Contrary to Popular Opinion Dershowitz selects his most recent columns, articles and essays and adds original commentary to present an engaging and spirited discussion from a remarkable mind about the most pressing issues of our time. Readers of Dershowitz's previous bestsellers, The Best Defense, Reversal of Fortune, and Chutzpah, will delight to see that Contrary to Popular Opinion continues Dershowitz's style of studied audacity. No matter how sensitive or incendiary the subject, Dershowitz is never afraid to say what is on his mind and back it up with solid and surprising arguments. In Contrary to Popular Opinion Dershowitz continues his crusade against blatant and subtle examples of anti-Semitism; dissects the "political correctness" controversy; exposes well-meaning censors on both the right and the left; blasts Bush's overtures to Beijing's repressive regime; makes a strong case for arresting and trying Yasir Arafat; questions the fairness of the RICO laws; makes a surprising pro-choice argument for the overturn of Roe v. Wade; wonders aloud about the damage the "war on drugs" is doing to our civil liberties; and condemns the ominous odor of fascism and bigotry rising from such diverse quarters as Russia's Pamyat and the Presidential campaigns of David Duke and Patrick Buchanan." "No matter what your political convictions, Alan Dershowitz is certain to delight and inform and possibly surprise you. In an age when political discourse has gone the way of the sound-bite, Alan Dershowitz provides a stimulating dose of that all-too-rare commodity - original thought compellingly presented."--BOOK JACKET